1982
DOI: 10.1002/ar.1092040109
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic polypeptide (PP)‐like immunoreactivity in the Pancreatic islets of the anglerfish (Lophius americanus) and the channel catfish (Ictalurus punctatus)

Abstract: Pancreatic polypeptide (PP) immunoreactivity was demonstrated in the endocrine pancreas of the anglerfish (Lophius americanus) and the channel catfish (Ictalurus punctatus) using immunohistochemistry. In both species, PP-immunoreactive cells were localized at the periphery of endocrine tissue. In Lophius americanus, PP-immunoreactivity could be localized in the principal islet, the pyloric or secondary islet, and the mesenteric or tertiary islets. A peripheral localization of PP-immunoreactive cells having cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

1984
1984
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The positive results of this comparative study of the endocrine pancreas in some Australian mammals are consistent with those of previous authors for other species (Larsson et al, 1975: Orci et al, 1976Gepts et al, 1978;Johnson et al, 1982), as well as with one of the postulates of the Bonner-Weir & Weir (1979) concept of mammalian endocrine pancreatic organization, i.e. the greater proportion of PP cells in the pancreatic head.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The positive results of this comparative study of the endocrine pancreas in some Australian mammals are consistent with those of previous authors for other species (Larsson et al, 1975: Orci et al, 1976Gepts et al, 1978;Johnson et al, 1982), as well as with one of the postulates of the Bonner-Weir & Weir (1979) concept of mammalian endocrine pancreatic organization, i.e. the greater proportion of PP cells in the pancreatic head.…”
Section: Discussionsupporting
confidence: 92%
“…In most species, they are found both within islets and scattered among the exocrine cells (Gepts, Baetens & DeMey, 1978). In islets, PP cells are preferentially located at the periphery (Larsson et al, 1975(Larsson et al, ,1976Orci, Baetens, Ravazzola, Stefan & Malaisse-Lagae, 1976;Johnson, Noe & Bauer, 1982). Paulin & Dubois (1978) have demonstrated that the PP cell is the last islet cell to differentiate in foetal life and consider it to be the most recently evolved.…”
Section: Introductionmentioning
confidence: 99%
“…As seen in Table 1, no significant differences were noted between any of the cell types of primary and secondary islets. While an antiserum against pancreatic polypeptide (PP) was not employed in this study, we assumed that the remaining unstained cells (8.4% in the primary islet and 3.9% in the secondary islet) represented cells containing PP, which has been previously localized in the catfish islet (Johnson et al, 1982).…”
Section: Resultsmentioning
confidence: 99%